Pro-Cyclical Petroleum Investments and Cost Overruns in Norway - Roy Endré Dahl; Sindre Lorentzen; Atle Oglend; Petter Osmundsen (Center for Economic Studies and ifo Institute (CESifo), 2016)
Development projects in the oil industry often have cost overruns. Through analysis of data from Norwegian development projects in the petroleum industry, this paper investigates the common effect of business cycle developments on cost overruns. Lack of capacity and expertise in a tight supplier market yield cost inflation and difficulties in managing projects. Unlike previous analyses of cost overruns, we analyse projects over a long time period to capture the cyclical effects. We document a statistically significant positive relationship between oil price developments and cost overruns, with shocks or surprises to the oil price during the project implementation having a larger impact on cost overruns than the oil price level itself. Cost overrun ultimately leads to reduced competitiveness for the industry, and we discuss consequences and policy implications for business and society of these cost overruns.
Keywords: D22; D24; G31; 330; cost overruns; petroleum projects; business cycle; oil price